Integrating RME and Geogebra: Transforming mathematics learning to support students’ mathematical literacy - Rizqi Adella (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2025)
The low mathematical literacy of Indonesian students as shown by the PISA results has become an issue in education. This study aims to analyze the effect of the Geogebra-assisted RME approach on students' mathematical literacy skills. This study applied a quantitative method with a One-Group Pretest-Posttest Design, which was carried out on 30 ninth grade students of SMP Negeri 2 Kapetakan, Cirebon Regency. The instruments used include a mathematical literacy test and student response questionnaires. Data were collected through test and questionnaire, then analyzed using N-gain and simple linear regression. The results showed that the average N-gain score of 0.85 was in the high category, which indicates a significant increase in mathematical literacy skills. In addition, the results of a simple linear regression test showed that the implementation of Geogebra-assisted RME had a positive and significant effect on students' mathematical literacy skills, with an R2 value of 0.337. These findings show that a contextual learning approach supported by interactive technology is effective in improving students' ability to understand, apply, and interpret mathematical concepts in real life. This research makes an empirical contribution to the integration of RME approaches and technology in geometry learning and mathematical literacy at the secondary level.